1、化简:\(\sqrt{1-2sin(\pi+2)cos(\pi+2)}\)
分析:\(\sqrt{1-2sin(\pi+2)cos(\pi+2)}=\sqrt{1-2sin2cos2}=\sqrt{(sin2-cos2)^2}=|sin2-cos2|=sin2-cos2\)
备注:\(2rad=2\times 57.3^{\circ},sin2>0,cos2<0,\).
2、已知\(x\)为第三象限的角,化简:\(\sqrt{(1-tanx)^2+(1+tanx)^2}\)
分析:\(\sqrt{(1-tanx)^2+(1+tanx)^2}=\sqrt{2+2tan^2x}=\sqrt{2}\cdot\sqrt{1+tan^2x}=\sqrt{2}\cdot\sqrt{1+\cfrac{sin^2x}{cos^2x}}=\sqrt{2}\cdot\sqrt{\cfrac{cos^2x+sin^2x}{cos^2x}}\)
\(=\sqrt{2}\cdot\sqrt{\cfrac{1}{cos^2x}}=\sqrt{2}\cfrac{1}{|cosx|}=-\cfrac{\sqrt{2}}{cosx}\)
3、化简:\(\sqrt{(1-sin\alpha sin\beta)^2-cos^2\alpha cos^2\beta}\),其中\(-\cfrac{\pi}{2}<\alpha<\beta<\cfrac{\pi}{2}\)
分析:\(\sqrt{(1-sin\alpha sin\beta)^2-cos^2\alpha cos^2\beta}=\sqrt{(1-sin\alpha sin\beta-cos\alpha cos\beta)(1-sin\alpha sin\beta+cos\alpha cos\beta)}\)
\(=\sqrt{(1-cos(\alpha-\beta))(1+cos(\alpha+\beta)}=\sqrt{2sin^2\cfrac{\alpha-\beta}{2}}\cdot 2cos^2\cfrac{\alpha+\beta}{2}=|2sin\cfrac{\alpha-\beta}{2}cos\cfrac{\alpha+\beta}{2}|\)
由于\(-\cfrac{\pi}{2}<\alpha<\beta<\cfrac{\pi}{2}\),可以得到\(-\pi<\alpha+\beta<\pi\),即\(-\cfrac{\pi}{2}<\cfrac{\alpha+\beta}{2}<\cfrac{\pi}{2}\),
故\(cos\cfrac{\alpha+\beta}{2}>0\);
同时能得到\(-\pi<\alpha-\beta<\pi\),且\(\alpha-\beta<0\),故\(-\pi<\alpha-\beta<0\),则\(-\cfrac{\pi}{2}<\cfrac{\alpha-\beta}{2}<0\),故\(sin\cfrac{\alpha-\beta}{2}<0\)
故原式\(=-2sin\cfrac{\alpha-\beta}{2}cos\cfrac{\alpha+\beta}{2}\)